Seroprevalence of hantavirus and Borrelia burgdorferi in Düzce (Turkey) forest villages and the relationship with sociodemographic features - AKAR, Nida (Turk J Med Sci, 2019)
BACKGROUND/AIM: Hantavirus and Borrelia burgdorferi are two zoonotic agents that pose a great risk especially for people living in forest areas. This study aimed to investigate the seroprevalence of hantavirus and B. burgdorferi in forest villages of Düzce and its relationship with sociodemographic features. MATERIALS AND METHODS: The presence of immunoglobulin M (IgM) and immunoglobulin G (IgG) antibodies against hantavirus and B. burgdorferi in serum samples was investigated via enzyme-linked immunosorbent assay (ELISA). Hantavirus IgG and B. burgdorferi IgM and IgG positivity was then validated by western blot (WB) method. RESULTS: During the analyses,193 serum samples were tested. Eleven (6%) cases of hantavirus IgM was found positive by ELISA. Six (3%) cases of hantavirus IgG, 3 (2%) cases of B. burgdorferi IgM, and 12 (6%) cases of B. burgdorferi IgG were found positive by WB. Borrelia burgdorferi IgG positivity was found to be higher in the 46–70 age group and it was seen that the positivity was the highest among those who lived in mud-brick houses. CONCLUSION: This study was the first to determine the frequency of hantavirus in the study region and it includes current data for B. burgdorferi. Consequently, it is recommended that similar studies be carried out on rodents in all the regions at risk.